Core Schemas in Youth at Clinical High Risk for Psychosis. Issue 2 (21st April 2015) - Stowkowy, Jacqueline; Liu, Lu; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; McGlashan, Thomas H.; Perkins, Diana O.; Seidman, Larry J.; Tsuang, Ming T.; Walker, Elaine F.; Woods, Scott W.; Bearden, Carrie E.; et al.
Abstract : Background: Schema Theory proposes that the development of maladaptive schemas are based on a combination of memories, emotions and cognitions regarding oneself and one's relationship to others. A cognitive model of psychosis suggests that schemas are crucial to the development and persistence of psychosis. Little is known about the impact that schemas may have on those considered to be at clinical high risk (CHR) of developing psychosis.Aims: To investigate schemas over time in a large sample of CHR individuals and healthy controls.Method: Sample included 765 CHR participants and 280 healthy controls. Schemas were assessed at baseline, 6 and 12 months using the Brief Core Schema Scale (BCSS). Baseline schemas were compared to 2-year clinical outcome.Results: CHR participants evidenced stable and more maladaptive schemas over time compared to controls. Schemas at initial contact did not vary amongst the different clinical outcome groups at 2 years although all CHR outcome groups evidenced significantly worse schemas than healthy controls. Although there were no differences on baseline schemas between those who later transitioned to psychosis compared to those who did not, those who transitioned to psychosis had more maladaptive negative self-schemas at the time of transition. Associations between negative schemas were positively correlated with earlier abuse and bullying.Conclusions: These findings demonstrate a need for interventions that aim to improve maladaptive schemas among the CHR population. Therapies targeting self-esteem, as well as schema therapy may be important work for future studies.